Dancing with the Surgeon: Neoadjuvant and Adjuvant Immunotherapies from the Medical Oncologist’s Perspective - Sehhoon Park (Journal of Chest Surgery, 2023)
Perioperative treatment with conventional cytotoxic chemotherapy for resectable nonsmall cell lung cancer (NSCLC) has proven clinical benefits in terms of achieving a higher overall survival (OS) rate. With its success in the palliative treatment of NSCLC, immune checkpoint blockade (ICB) has now become an essential component of treatment, even as neoadjuvant or adjuvant therapy in patients with operable NSCLC. Both pre- and post-surgery ICB applications have proven clinical efficacy in preventing disease recurrence. In addition, neoadjuvant ICB combined with cytotoxic chemotherapy has shown a significantly higher rate of pathologic regression of viable tumors compared with cytotoxic chemotherapy alone. To confirm this, an early signal of OS benefit has been shown in a selected population, with programmed death ligand 1 expression ≥50%. Furthermore, applying ICB both pre- and post-surgery enhances its clinical benefits, as is currently under evaluation in ongoing phase III trials. Simultaneously, as the number of available perioperative treatment options increases, the variables to be considered for making treatment decisions become more complex. Thus, the role of a multidisciplinary team-based treatment approach has not been fully emphasized. This review presents up-to-date pivotal data that lead to practical changes in managing resectable NSCLC. From the medical oncologist’s perspective, it is time to dance with surgeons to decide on the sequence of systemic treatment, particularly the ICB-based approach, accompanying surgery for operable NSCLC.